Laparoscopic‐endoscopic cooperative surgery is a safe and effective treatment for superficial nonampullary duodenal tumors. Issue 4 (November 2015) - Kyuno, Daisuke; Ohno, Keisuke; Katsuki, Shinichi; Fujita, Tomoki; Konno, Ai; Murakami, Takeshi; Waga, Eriko; Takanashi, Kunihiro; Kitaoka, Keisuke; Komatsu, Yuya; Sasaki, Kazuaki; Hirata, Koichi
Abstract: The use of endoscopic submucosal dissection (ESD) for duodenal neoplasms has increased in recent years, but delayed perforation and bleeding are also known to frequently occur. We present two cases in which duodenal adenoma was successfully treated with laparoscopic‐endoscopic cooperative surgery. ESD was combined with laparoscopic seromuscular sutures. The lesions in both cases were located in the second portion of the duodenum. The patients requested resection of the lesion, and we performed laparoscopic‐endoscopic cooperative surgery. After the laparoscopic surgeon mobilized the duodenum, the endoscopic surgeon performed ESD for the duodenal tumor without perforation. The laparoscopic surgeon sutured the duodenal wall in the seromuscular layer to strengthen the ulcer bed after ESD. Histopathological studies confirmed that the surgical margins were tumor‐free in both cases. The patients were discharged with no complications. This unique laparoscopic‐endoscopic cooperative procedure is a safe and effective method for resecting superficial nonampullary duodenal tumors.